Motor Skills Increase In The Learning Model Of Circuit Games - Palupi Ardanari; Nurhasan Nurhasan; Abdulrahman Syam Tuasikal (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to prove the effect of the circuit games learning model on students' motor skills through the motor fitness test instrument. Motoric abilities start from basic locomotor and non-locomotor movements to the occurrence of manipulative movements in students. Motoric abilities are thought to be able to develop students' movement and physical abilities. 30 students of SDN Kendalbulur I were selected consecutively to take part in the study using the circuit games learning model experiment. The research instrument used the motor fitness test. The statistical test uses an influence test using the pre and post-test format. The results showed that all motor fitness test items experienced an increase in value before and after the circuit games learning model was implemented (p <0.05). This shows that the motor skills of students have increased after learning is done. Recommendations from the results of the research are that PJOK teachers can apply game-based learning models, especially in circuit games. Furthermore, other game-based learning models are studied to be able to complement the learning model of circuit games.